Cambios en la adaptación escolar en la época post-COVID 19 en estudiantes de preescolar en el municipio de Maicao, La Guajira - Ivana Marcela Villalobos Boscan; Paula Camila Ariza Madera (Universidad Antonio Nariño, 2025)
The general objective of this research is to explore the changes in school adaptation in the post-COVID 19 period in preschool students as perceived by teachers at the Educational Institution Nº11 Sede el Carmen in the municipality of Maicao, La Guajira. For its development, a quantitative study was carried out using the survey to collect the information, which was applied to a sample of ten (10) high school teachers of the Educational Institution Nº11 Sede el Carmen of the municipality of Maicao, who were selected through criterion or deliberate sampling. With this, the results of the investigation were dazzled where 66% of the teachers report negative changes in the academic performance, however, in their majority they think that the young people do not present interaction and bonding problems